A influência das áreas verdes urbanas na configuração da paisagem do bairro Jabotiana à luz da ética ambiental - Barros, Manuela Alves Lima (2019)
This research aims to examine the remaining urban green areas of the Jabotiana neighborhood in Aracaju-SE in light of the reflection of gardens and green spaces in the design of cities. In this way, the formation of the urban green was examined and how the cities were drawn over time with their gardens. In addition, the relationship of environmental ethics and the progress of science to the relations of good use of nature by men was examined. In order to achieve the proposed objectives, this study used the hypothetic-deductive method of Karl Popper, who understands that the scientific method starts from a problem in which a kind of provisional solution or a tentative theory is offered. In accordance with the above method, we formulated the following working hypothesis: Existing urban public green areas, which originate from the divisions of properties in the district of Jabotiana and that are identified in the SEFIN real estate register, are without use, without plant cover or are being underutilized by the Municipality of Aracaju, thus failing to fulfill its social function. This research also presents a conceptual proposal for the term "green areas" as a guiding base in order to identify these spaces in the neighborhood. In this sense, this dissertation was structured, basically in four chapters. The first deals with the construction of urban green areas throughout history, the progress of urbanism and the relations of good use of nature. The second chapter presents a conceptual proposal based on scholars on the subject; as is the relation of green in some of the main cities of the world and in Brazil. In the third, cartographic data and illustrations are used, which will identify all the municipal green areas in the Jabotiana neighborhood, originated from a donation. Finally, in the fourth chapter, a survey is made of all areas of the neighborhood where there may still be donations coming from future installments in light of the transformations arising from the process of new occupations. Thus, in view of the urbanization of the neighborhood, possible perspectives are presented for the use of green areas from future subdivisions, as well as improvements in the existing typologies, where good-nature relationships are allowed between man and nature with adequate socio-environmental integration.